The Effect of Emotional Regulation and Social Support on Self-Efficacy Among Inmates with Drug Abuse Problems Undergoing Conditional Release Programs at Banceuy Class IIA Prison - Fio Ananta Putri; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Drug abuse, psychotropic drugs, and addictive substances are among the causes of the increasing number of inmates in Indonesia. The conditional release program at the Banceuy Class IIA Correctional Institution requires psychological support, such as emotional regulation skills, social support, and self-efficacy. This study aims to describe how inmates with a history of substance abuse regulate their emotions and obtain social support, as well as analyze the influence of these two factors on their level of self-efficacy. This study uses a quantitative method with a multiple linear regression design. Data were collected on December 2, 2025, from 50 inmates using the emotion regulation, social support, and self-efficacy scales. The results of the analysis show that emotion regulation and social support together have a significant effect on self-efficacy (F = 15.102; p < .001), accounting for 39.1% of the variance (R Square = 0.391). Individually, emotional regulation had a negative and significant effect on self-efficacy (B = –0.468, t = –3.374, p = .001), while social support had a positive and significant effect on self-efficacy (B = 0.767, t = 5.454, p < .001). These findings indicate that inappropriate regulation can reduce the self-efficacy of inmates, while strong social support actually increases their self-efficacy in undergoing the parole program.